(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article is about comparative semantic analysis of phraseological units which express positive evaluation of the person in English and Uzbek. It is also analyzed etimology of several phraseologisms expressing positive emotional evaluation in both languages.